Pengenalan Bahasa Isyarat Berbasis Android - Hazkia, Hazkia; Wahyuddin, Wahyuddin (Fakultas Teknik Universitas Muhammadiyah Parepare, 2024)
Deaf students have hearing impairments, so they cannot hear sounds perfectly. This limitation results in the learning process being hampered. This research aims to create learning media for deaf sign language codes using 3D image-augmented reality technology. The research method uses descriptive quantitative methods with the help of the augmented reality application Vuforia and Unity on Android mobile devices, using three samples and a distance of between 20 and 50 cm and using degrees of dryness. The results show that the letters A and B are not visible at a distance of 20 cm, while the letter C is visible. At 30-650 degrees of inclination, the letters A-C are not visible, while at 70-900 degrees they are. This is caused by the quality of the detected object and inadequate lighting.